diff -r 78a82c37b4b2 -r 484559628038 src/HOL/Imperative_HOL/ex/Sublist.thy
--- a/src/HOL/Imperative_HOL/ex/Sublist.thy Thu Jun 18 16:17:51 2015 +0200
+++ b/src/HOL/Imperative_HOL/ex/Sublist.thy Fri Jun 19 15:55:22 2015 +0200
@@ -471,26 +471,26 @@
unfolding set_sublist' by blast
-lemma multiset_of_sublist:
+lemma mset_sublist:
assumes l_r: "l \ r \ r \ List.length xs"
assumes left: "\ i. i < l \ (xs::'a list) ! i = ys ! i"
assumes right: "\ i. i \ r \ (xs::'a list) ! i = ys ! i"
-assumes multiset: "multiset_of xs = multiset_of ys"
- shows "multiset_of (sublist' l r xs) = multiset_of (sublist' l r ys)"
+assumes multiset: "mset xs = mset ys"
+ shows "mset (sublist' l r xs) = mset (sublist' l r ys)"
proof -
from l_r have xs_def: "xs = (sublist' 0 l xs) @ (sublist' l r xs) @ (sublist' r (List.length xs) xs)" (is "_ = ?xs_long")
by (simp add: sublist'_append)
- from multiset have length_eq: "List.length xs = List.length ys" by (rule multiset_of_eq_length)
+ from multiset have length_eq: "List.length xs = List.length ys" by (rule mset_eq_length)
with l_r have ys_def: "ys = (sublist' 0 l ys) @ (sublist' l r ys) @ (sublist' r (List.length ys) ys)" (is "_ = ?ys_long")
by (simp add: sublist'_append)
- from xs_def ys_def multiset have "multiset_of ?xs_long = multiset_of ?ys_long" by simp
+ from xs_def ys_def multiset have "mset ?xs_long = mset ?ys_long" by simp
moreover
from left l_r length_eq have "sublist' 0 l xs = sublist' 0 l ys"
by (auto simp add: length_sublist' nth_sublist' intro!: nth_equalityI)
moreover
from right l_r length_eq have "sublist' r (List.length xs) xs = sublist' r (List.length ys) ys"
by (auto simp add: length_sublist' nth_sublist' intro!: nth_equalityI)
- ultimately show ?thesis by (simp add: multiset_of_append)
+ ultimately show ?thesis by (simp add: mset_append)
qed